Ответ:
Пошаговое объяснение:
<h2>
x²(x-5)³-36x+180=</h2><h2>
=x²(x-5)³-36(x-5)=</h2><h2>
=(x-5)((x(x-5))²-6²)=</h2><h2>
=(x-5)(x²-5x-6)(x²-5x+6)=</h2><h2>
=(x-5)(x-6)(x+1)(x-2)(x-3)</h2>
---------------------------
по т Виета x²-5x-6=(x-6)(x+1)
x²-5x+6=(x-2)(x-3)
формула разность квадратов: x²-y²=(x-y)(x+y)
90+7=97
97-45=х или 52
проверка-52+45=97=90+7
1) 0.25=0.125+0.25х
0.125=0.25х
х=0.5
2) 0.5=0.125+0.25х
0.375=0.25х
х=1.5
3) 10=0.125+0.25х
9.875=0.25х
х=39.5
15.40+3.50=в 19.30ч дядя Федор приехал в Простоквашино
Дробью 10 третьих или 3 целых одна третья